Cultura digital: definições, elementos constituintes, aspectos históricos e a relação com memória (função cognitiva) e mentes estendidas - Silva, Josiane Rosa da (2016)
The work deals with the relationship between technology and knowledge, realizing that the former are not merely accessories and devices, but interfere in the course of culture. Just as language, developed by human intelligence, it facilitated the communication between individuals of a society, unfolding into many languages that make up the identity of people and their culture, so the technology is a creation of man that returns on he and turns. In today's world, we experience a profound cultural change in the way to acquire and produce knowledge is collaborative. Among the cognitive aspects involved in the transformations brokered by digital culture, the work highlights the memory, and its implications in the constitution of culture and of individual and collective identity. The individual is reflected and portrayed on the other. The process of training and consecutive alternation of the subject is not of his own conscience, but it's consolidated socially, through the interactions of words, the virtual world. The paper questions how the use of digital relates to memory tools, taking into account the notion of mind extended by technologies. To do so, it resorted to extensive literature review, which highlighted Vilém Flusser, James Gleick, Jaques Le Goff and Andy Clark